β-Glucan-Functionalized Nanoparticles Down-Modulate the Proinflammatory Response of Mononuclear Phagocytes Challenged with Candida albicans - Tânia Lima; Stefán B. Gunnarsson; Elisabete Coelho; Dmitry V. Evtuguin; Alexandra Correia; Manuel A. Coimbra; Tommy Cedervall; Manuel Vilanova (Nanomaterials, 2022)
Systemic fungal infections are associated with significant morbidity and mortality, and Candida albicans is the most common causative agent. Recognition of yeast cells by immune cell surface receptors can trigger phagocytosis of fungal pathogens and a pro-inflammatory response that may contribute to fungal elimination. Nevertheless, the elicited inflammatory response may be deleterious to the host by causing excessive tissue damage. We developed a nanoparticle-based approach to modulate the host deleterious inflammatory consequences of fungal infection by using β1,3-glucan-functionalized polystyrene (β-Glc-PS) nanoparticles. β-Glc-PS nanoparticles decreased the levels of the proinflammatory cytokines TNF-α, IL-6, IL-1β and IL-12p40 detected in in vitro culture supernatants of bone marrow-derived dendritic cells and macrophage challenged with C. albicans cells. Moreover, β-Glc-PS nanoparticles impaired the production of reactive oxygen species by bone marrow-derived dendritic cells incubated with C. albicans. This immunomodulatory effect was dependent on the nanoparticle size. Overall, β-Glc-PS nanoparticles reduced the proinflammatory response elicited by fungal cells in mononuclear phagocytes, setting the basis for a targeted therapy aimed at protecting the host by lowering the inflammatory cost of infection.